The Last Mile: Using Local Knowledge to Identify Barriers to Sustainable Grain Legume Production - Smith, Barbara M.; Gathorne-Hardy, Alfred; Chatterjee, Soumik; Basu, Parthiba (Frontiers in Ecology and Evolution, 2018)
Grain legumes (or pulses–annual leguminous crops that are harvested solely for their dried seeds such as lentils or chickpeas) are essential for sustainable cropping systems. They positively contribute to soil fertility and agricultural biodiversity and are a highly nutritious food source, yet they remain under-exploited across the world. In India–soon to be the world's most populous country and the world's largest importer, producer and consumer of pulses–they are substantially under-utilized and are the only major food group not to have increased in output since independence in 1947. Existing efforts to address low grain legume production have focused on the scientific and agronomic barriers, with little impact on productivity. In contrast, this project, using Tripura in India as a case study, recognizes the limits of imposing top-down solutions and instead focuses on the barriers to production as identified by the growers themselves. Working with 440 farmers from 19 non-tribal and 11 tribal villages in Tripura, NE India, we used facilitated discussion to identify their key barriers to pulse production, and facilitated pile sorting to identify the commonly consumed, grown and available pulses. Twenty-eight barriers to legume production were identified by farmers. The eight principal barriers were: insufficient water; lack of technical knowledge; unreliable seed supply; lack of processing units; soil fertility; financial constraints; limited fertilizer supply; and insufficient fencing material. These barriers are complex and overlapping and originate from system level failures to sufficiently prioritise grain legumes compared to cereals. However, recognizing the length of time it takes to address system level problems, in this paper we identify five immediately applicable mitigating strategies to help overcome the principle barriers identified here. Importantly, these will also create an improved environment to apply the technologically sophisticated grain legume R&D that has been carried out over the last 20 years but has yet to have a measurable impact on pulse production. Therefore understanding the wider socio-economic pathways to sustainable pulse production is essential to facilitate change on the ground. Our results, relevant to policy makers in India and around the world, demonstrate the value of listening to farmers when attempting to improve production, and emphasize the necessity of including the socio-economic systems surrounding pulse production, to complement the current emphasis on biological barriers.